Capacity development efforts to support national implementation of the International Treaty on Plant Genetic Resources for Food and Agriculture: Activities and lessons learned - Tsioumani, Elsa; Adetiloye, Ibidun; Aladele, Sunday; Buldawoo, Indranee; Chiarolla, Claudio; Chipfunde, Onismus; Condón, Federico; Dulloo, Ehsan; German Castelli, Pierina; Halewood, Michael; Kombate, Koffi; Lopez Noriega, Isabel; et al. (2025)
This policy brief outlines the outcomes of a study on the effectiveness of capacity development efforts in the six countries supported by the Genebanks Accelerator in the 2022-2024 period, including achievements, challenges, and lessons learned. It takes stock of the status of implementation of the MLS, compares national approaches, and identifies main capacity needs and gaps. It is based on a desk review of project documents and workshop reports, an analysis of the legal and policy instruments developed in the six project countries, and 11 interviews with national project partners. The Plant Treaty’s Capacity Development Strategy and its draft action plan, as well as a number of CGIAR’s submissions and tools, were also used to frame the analysis.